Feasibility Study for Installing Machine in Production Line to Avoid Particle Contamination Based on CFD Simulation - Adisorn Khaokom; Jatuporn Thongsri (My University, 2017)
Ventilation system inside production line for electronic component production needs to meet the factory standard. Because it can eliminate small particles which may cause of human or machine in production as well as it can distribute the circulating air temperature uniformly. CFD is used in this research in order to study the feasibility and plan for machine layout in production line before actual installation. The simulation shows the airflow in every area inside production line. From simulation with releasing the particles from human and machine is found that this ventilation system generates airflow that makes most particles float out of the machines and no particle downs to the conveyor, it results to contamination. In addition, the simulation also shows the range of 19-26 °C air temperature that meets the factory standard. The results of this research are the parts of the data to renovate the production line to get more efficiency and proper on the production.
Keywords: Production line; Factory (object-oriented programming); Installation; Particle (ecology); Vehicle emissions and performance